Electronic Revenue Registry in the Czech Republic - Radvan, Michal; Kappel, Jiří (LeXonomica, 2015)
In the Czech Republic there is an on-going debate and for the last year also legislative work on a Revenue Registry Act. This article introduces the system of revenue registry which should be applied in the Czech Republic, critically analyses fundamental provisions of the draft bill and summarizes advantages and disadvantages of the regulation and its strength, weaknesses, opportunities and threats. Article deals with a hypothesis that implementation of revenue registry will fulfil the goals of the proposed regulation i.e. new source of data for tax administration, restriction of grey economy, more efficient tax collection, especially of income tax and VAT and also elimination of market inequalities in the Czech economy.